The effect of foliar spray with some nutrients and citric acid on the productive qualities of the Valencia orange grafted on citrumelo as root stock (Latakia University Journal -Biological Sciences Series, 2023)
The study was carried out during (2020 and 2021) at Setkhiris village which belonging to the countryside of Lattakia Governorate, in citrus orchard containing (36) trees of citrus paradise at the age of 25 years old and grafted on citrumelo as root stock, to study the impact of foliar spray with mixture of macronutrients (N,P,K)(2 g/l) , mixture of micronutrients (Fe,B,Mg,Zn) (1g/l) and citric acid(1 g/l) , on the growing and fruiting properties of the Valencia orange. The results showed positive effects of the treatments in improving vegetative growth parameter, flowering , fruiting and  fruit production compared to the control , at treatment of multi fertilization with mixture of macronutrients, mixture of micronutrients and citric acid spray achieved the highest number of vegetative growths (15),and The highest percentage of the contract was (63.24%), and the same treatment gave the highest percentage of the fruiting coefficient (4.28%). as The treatment of spraying with macroelements and citric acid gave the highest value of total chlorophyll content (3.52).